Construction and Encapsulation of Colloidal Vesicles Based on Bovine Serum Albumin-Dextran Interfacial Assembly - Qianqian GUO; Dan LI; Yongli YANG; Li LI; Gaoyang YI; Xiaolin YAO (Shipin gongye ke-ji)
As colloidal structural components, the colloidal vesicles formed by the modified proteins and polysaccharides were a unique type of artificial cells with good membrane permeability, so they were widely used in cell engineering, biosensing, drug delivery and functional foods. Based on this, this study aimed to construct colloidal vesicles with aminoized bovine serum albumin (BSA-NH2) and carboxylated dextran (DEX-COOH) as the building blocks, and use Pickering emulsion template method to optimize complex concentration, oil/water volume ratio and crosslinker concentration. The storage stability at different temperatures and the ability to contain dextran with different molecular weight were investigated. Results showed that colloidal vesicles with stable morphology, uniform dispersion, stable smooth spherical shape and complete membrane structure were obtained under the conditions of compound concentration of 20 mg/mL, oil/water volume ratio of 10:1 and crosslinker concentration of 0.75 mg/mL, with size of 4.29±1.11 μm. The vesicles were stable at 4 ℃ on 0, 4 and 7 d, with sizes of 5.13±1.15, 4.81±1.03 and 5.01±1.33 μm, respectively, and could effectively contain dextran with molecular weight ≤70 kDa. Therefore, the vesicles can be used as an effective carrier of hydrophilic active components and widely used in food active component delivery.